KETERKAITAN STRUKTUR PEKERJAAN DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PT. TANTO INTIM LINE DI SAMARINDA - Sattar; Moh. Romadloni; H.M. Andreas Y. Sutrisno; Amrin Buton (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
Referring to the problem, it can be concluded that based on the F test, the variables of Job Structure and Individual Characteristics simultaneously or jointly have a significant effect on the Performance of Employees of PT. Tanto Intimate Line In Samarinda. Then the t-test, then the variable Job Structure partially significant effect on the performance of employees of PT. Tanto Intimate Line In Samarinda. Then the Individual Characteristics variable has a significant effect on the Employee Performance of PT. Tanto Intimate Line In Samarinda. Furthermore, the correlation test describes the close relationship between the independent variable and the dependent variable. The correlation value of 0.683 means that this value has a strong relationship between the work structure and individual characteristics of the employee performance of PT. Tanto Intimate Line In Samarinda. Meanwhile, based on the value of R square 0.466 or 46.4%, it means that the variable of Job Structure and Individual Characteristics on Employee Performance of PT. Tanto Intim Line in Samarinda has a percentage relationship of 46.6% to the Effect of Work Structure and Individual Characteristics on Employee Performance at PT. Tanto Intim Line in Samarinda, while the remaining 53.4 are influenced by other variables such as human resources, work motivation, work environment, and so on.